Зрительная система пауков-скакунчиков (Aranei, Salticidae). I. Принципы организации - Пичка, В.Е. (Вестник зоологии, 1981)
The general perceptive field in spiders (Salticidae) is differentiated according to the principle of optic functions’ distribution between separate eyes. The light-percepting apparatus of the optic system consists of the perceptive fields of two main and four accessory eyes (posteromedial eyes are rudimentary). The multilayer retina of main eyes from the physiologically standpoint is a “pit” spatially distinguished in the homogeneous perceptive field of accessory eyes. The system of the main eye and the system of accessory eyes are differentiated according to their connections with the associative brain centres. The main eye system includes two optic ganglia. The ipsilateral accessory eyes' system involves three optic ganglia: two first ganglia (of the anterolateral and posterola teral eyes) and one second ganglion (common for ipsilateral accessory eyes). Contralateral eye systems in the spider brain are not united at the projection level, this resulting in the absence both of a single picture of the environment and the material basis for obtaining stereoscopic perception of the space. The best vision zone is clearly distinct in the general perceptive field and has an individual connection with the associative brain, centres. The general perceptive field of the spiders cannot be compared with the perceptive field of the compound eyes in insects. It may be concluded that representatives of the Araneida order possess a peculiar principle of the optic system organization differing from the principles in vertebrates and insects.